Human Rights Mechanisms for the Protection of Women and Children from Enforced Disappearance - Janina, Suela (Mediterranean Journal of Social Sciences, 2012)
Gender inequality is one of the most pervasive forms of social inequality and is often exacerbated by conflict and situations ofgross human rights violations. Enforced disappearance can be among the factors leading to deterioration in the living conditions ofwomen and girls, poverty, violence, multiple forms of discrimination and the limitation or denial of their human rights. The fact thatwomen around the world already suffer from unequal status and treatment compared with men magnifies the difficulties they face asrelatives of the disappeared. The enforced disappearance of children is an especially disturbing practice and complex in the issues towhich it gives rise legally, morally and socially. The disappearance of a child is a clear contravention of a number of provisions of theConvention on the Rights of the Child. This article aims to analyze the legal mechanisms provided by human rights treaties for theprotection of women and children as vulnerable groups affected by enforced disappearance. The focus of the analyze is concentrated onthe UN Convention against enforced disappearance as the universal legal instrument for the protection of all persons from thisinternational crime. Some recommendations will be provided for the state parties to implement legislation and policies aimed to protectand promote the rights of women and children.